2002
DOI: 10.1038/sj.eye.6700157
|View full text |Cite
|
Sign up to set email alerts
|

Partial coherence laser interferometry vs conventional ultrasound biometry in intraocular lens power calculations

Abstract: Aims The purpose of the study was to compare optical biometry based on partial coherence laser interferometry (PCLI) principle to conventional ultrasound biometry in the accuracy of intraocular lens (IOL) power calculations. The role of partial coherence laser interferometry in pseudophakic axial length measurement was analysed in the study. Methods In a prospective randomised clinical trial, 100 patients undergoing phacoemulsification cataract surgery were randomised to undergo biometry by either partial cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
22

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(179 citation statements)
references
References 19 publications
5
136
0
22
Order By: Relevance
“…In a comparative study of 50 cataractous eyes, pre and postoperatively, Packer et al 23 found that 92% of them were within 0.50 D and 100% were within 1 D of the targeted refraction; IOL power was computed from the IOLMaster using the Holladay II formula. Two other studies 7,24 showed that a high percentage of patients (87 and 91%) assigned to IOLMaster biometry achieved targeted refraction of within 1 D, compared with about 80% in the applanation group. In another study, 25 the two figures were even reported to be as high as 96 and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative study of 50 cataractous eyes, pre and postoperatively, Packer et al 23 found that 92% of them were within 0.50 D and 100% were within 1 D of the targeted refraction; IOL power was computed from the IOLMaster using the Holladay II formula. Two other studies 7,24 showed that a high percentage of patients (87 and 91%) assigned to IOLMaster biometry achieved targeted refraction of within 1 D, compared with about 80% in the applanation group. In another study, 25 the two figures were even reported to be as high as 96 and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite these shortcomings, ultrasound biometry may be the only means of obtaining suitable biometry in problematic cases: eyes with dense ocular media, 5 low visual acuity, 6 and fixation instability caused by macular degeneration. 7 IOLMaster has been reported to be ineffective in B20% of cataract patients 8 in the UK public hospitals, many of whom have posterior subcapsular cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from clinical studies have shown that if the guidelines on formulae are applied and in addition A constants are customised and immersion ultrasound or partial coherence interferometry is used for axial length measurement then more than 90% of eyes would achieve a prediction error of o1.0 dioptre. [2][3][4] This standard far exceeds what most departments in the United Kingdom (UK) are currently delivering when using a single formula for all eyes without customising A constants. 5 The first National Biometry Audit performed in 2002 and published in Eye in January 2004 concluded that there was very poor awareness and implementation of the guidelines with only 4% of eye departments fully complying with the recommendations regarding IOL calculation formulae.…”
Section: Introductionmentioning
confidence: 99%
“…O cálculo do poder refrativo da LIO, determinado antes do procedimento cirúrgico, é essencial e de extrema importância para atingir um estado emétrope (Erkin et al, 1999), apesar de Ranzani et al, 2008 terem constatado em cães normais, uma tendência à hipermetropia, ao efetuarem retinoscopia com luz em faixa. No passado, as LIO eram calculadas utilizando-se fórmulas analíticas baseadas na óptica de Gaussian.…”
Section: Introductionunclassified